Proteomic signatures of retinal pigment epithelium-derived exosomes in myopic and non-myopic tree shrew eyes - Sanchez, Nilda C.; Roig-Lopez, Jose Luis; Mobley, James A.; Khanal, Safal (Frontiers in Medicine, 2025)
PurposeThe retinal pigment epithelium (RPE) transmits growth signals from the neural retina to the choroid in the emmetropization pathway, but the underlying molecular mechanisms remain poorly understood. Here, we compared the proteomic profiles of RPE-derived exosomes between myopic and non-myopic eyes of tree shrews, dichromatic mammals closely related to primates.MethodsFour myopic (159–210 days of visual experience, DVE) and seven non-myopic eyes (156–210 DVE) of tree shrews were included. Non-cycloplegic refractive error was measured with Nidek autorefractor, and axial ocular component dimensions were recorded with LenStar. Tissue was collected, yielding RPE-lined eyecups, which were subsequently incubated in L-15 culture media for 2 h. The RPE-derived exosomes were then enriched and purified from the incubation media by double ultracentrifugation and characterized by imaging and molecular methods. Exosomal proteins were identified and quantified with mass spectrometry, examined using GO and KEGG analyses, and compared between myopic and non-myopic samples.ResultsOut of 506 RPE exosomal proteins identified, 48 and 41 were unique to the myopic and non-myopic samples, respectively. There were 286 differentially expressed proteins in the myopic samples, including 79 upregulated and 70 downregulated. The top three upregulated proteins were Histone H4 (Fold Change, FC = 3.04, p = 0.09), PTB 1 (FC = 2.59, p = 0.08) and Histone H3.1 (FC = 2.59, p = 0.13), while the top three downregulated proteins were RPS5 (FC = −2.41, p=0.004), ACOT7 (FC=-2.15, p = 0.04) and CRYBB2 (FC = −2.14, p = 0.05). Other differentially expressed proteins included LUM, VCL, SEPTIN11, GPX3, SPTBN1, SEPTIN7, RPL10A, KCTD12, FGG, and FMOD. Proteomic analysis revealed a low abundance of ATP6V1B2 and crystallin beta B2, and a significant depletion of the crystallin protein family (crystallin A2, A3, and B3 subunits) in the myopic samples. The enrichment analyses showed extracellular matrix, cytoskeletal dynamic, and cell-matrix adhesion as the primary components associated with the RPE exosomal proteins in myopic eyes.ConclusionUsing standard molecular and imaging techniques, this study provides the first demonstration of the ex-vivo RPE exosome biogenesis from tree shrew eyes. The results showed distinct differential expressions of the RPE exosomal proteins between the myopic and non-myopic eyes, with several proteins unique to each group. Future targeted proteomic studies of identified candidate exosomal protein signatures could elucidate the molecular mechanism of RPE exosome-mediated growth signal transmission in the emmetropization pathway.